1977
DOI: 10.1002/bjs.1800640917
|View full text |Cite
|
Sign up to set email alerts
|

Serum ionized calcium in acute pancreatitis

Abstract: Measurement of serum ionized calcium was performed daily for 7 days after admission in 8 consecutive patients with acute pancreatitis. The results support the findings of our previous study that the most common cause of the low serum calcium often found in patients with this disease is a low serum albumin; when correction of serum calcium is made for hypo-albuminanemia, most patients are found to be normocalcaemic. The occasional hypocalcaemia as shown by the 'corrected' serum calcium or by serum ionized calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 19 publications
2
10
0
1
Order By: Relevance
“…He was not given the glucose-insulin-potassium infusion therapy which had previously proved beneficial. Both clinically and biochemically, he was similar to a patient with features of the sick cell syndrome (Flear and Singh, 1973), who was reported in our earlier study (Allam and Imrie, 1977).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…He was not given the glucose-insulin-potassium infusion therapy which had previously proved beneficial. Both clinically and biochemically, he was similar to a patient with features of the sick cell syndrome (Flear and Singh, 1973), who was reported in our earlier study (Allam and Imrie, 1977).…”
Section: Discussionsupporting
confidence: 82%
“…is serum albumin in g/l and Ca (corrected) is serum calcium in mmol/l corrected for albumin. The full derivation of this formula, its validation and the methods used in the measurement of total serum calcium, albumin and phosphate have previously been described in detail (Imrie et al, 1976;Allam and Imrie, 1977). The normal serum calcium level for our laboratory is 2.20-2.60 mmoljl, albumin 42-52 g/l (purified human albumin used as a standard).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypokalemia and polyuria in patients with leptospirosis suggest an increase in distal potassium secretion secondary to increased distal sodium delivery 32 . Ionic hypocalcemia was also observed and could be due to rhabdomyolysis or acute pancreatitis 1,24,27,36 .…”
Section: Discussionmentioning
confidence: 99%
“…It is a marker of severe pancreatitis and is one of the early signs in Ranson's criteria [23], Fan et al [24] found that elevated serum urea (>7.4 mmol/1) and glucose (> 11.0 mmol/1) levels correlated with the severity of acute attack. Certain acute phase reactants in the serum or urine of patients are predictive of severe acute pancreatitis, for example, a^-macroglobulin [25], urinary trypsinogen activation peptide [26] and granulocytic elastase [27], Peak or 7th-day level of serum C-reactive pro tein concentration provides comparable accu racy to Ranson's criteria in predicting severe acute pancreatitis [28].…”
Section: Single-sign Criteriamentioning
confidence: 99%